Administrative Procedures Salesman's Business Trip - Bunga Hadist Tira; Titim Nurlia (IJESS International Journal of Education and Social Science, 2026)
Salesman administration travel procedures are crucial for supporting the smooth operation of a company, particularly in marketing activities and achieving sales targets. Structured travel administration is essential for ensuring the effective submission, implementation, and accountability of expenses in accordance with company policy. This final project examines the salesperson travel administration procedures at PT Gandum Mas Kencana, the challenges encountered during implementation, and the company's solutions to address these challenges. The research method used is descriptive with a qualitative approach through observation, interviews, and literature review. The results indicate that the salesperson travel administration procedures are well-functioning and supported by a structured administrative system. However, several challenges remain, including changes to travel schedules, lengthy approval processes, and missing or incomplete expense documentation. To address these challenges, the company is improving coordination, reviewing reports, and implementing more effective travel planning.